Ketahanan Bending Komposit Hybrid Serat Batang Kelapa/Serat Gelas Dengan Matrik Urea Formaldehyde - Herlina Sari, Nasmi; -, Sinarep; Taufan, Ahmad; Yudhyadi, IGNK (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011)
The composite has its own advantages compared to other alternative techniques such material is strong, lightweight,corrosion-resistant, economical and so on. The purpose of this study was to investigate the characteristics of bending strengthfiber composite hybrid coconut trunk / fiber glass using urea formaldehyde resin.Hybrid palm trunk fiber /glass fiber composite have been made by hand lay up which volume fraction fiber hybridvariation namely 10:20, 15:15 and 20:10 (%) with length fiber 2 cm. Every Tests conducted were bending testing with eachvariation performed three times repetition. Bending test specimens in accordance with standard ASTMD 790.The results of bending strength of palm trunk fiber hybrid composite / fiber-glass with random fiber direction that thehighest bending strength in the palm trunk fiber volume fraction 10% and 20% glass fiber that is 22.7 N/mm2.
Keywords: Fiber Hybrid, palm trunk fiber, fiber glass, Bending, urea formaldehyde.